A DInSAR Investigation of the Ground Settlement Time Evolution of Ocean-Reclaimed Lands in Shanghai - Zhao, Qing; Pepe, Antonio; Gao, Wei; Lu, Zhong; Bonano, Manuela; He, Man L.; Wang, Jun; Tang, Xi (IEEE journal of selected topics in applied earth observations and remote sensing, 2015)
Reclaimed lands are seriously affected by ground settlement episodes, which are primarily caused by unconsolidated soils, and could result in severe damage to buildings and public infrastructures. In this work, we present a differential synthetic aperture radar (DInSAR) analysis of the ground displacement that impacts the ocean-reclaimed areas of the Nanhui New City of Shanghai (China), based on jointly exploiting persistent scatterers (PS) and small baseline (SB) approaches. The mean line of sight displacement velocity maps and the corresponding interferometric time-series of deformation were initially cross-compared to assess the accuracy of both DInSAR techniques in regions subject to long-lasting land reclamation processes. By exploiting a set of 31 SAR images collected by the ASAR/ENVISAT sensor from February 2007 to May 2010, we found the average difference between PS and SB velocity maps at 1.2 mm/year, with a root mean square difference of 5 mm for single measurements. Despite the increased levels of noise in the interferograms, due to the extremely time-varying electromagnetic and geometrical characteristics of the SAR scenes in correspondence to reclamation platforms, these results suggest that during first stages of reclamation processes both DInSAR methods are able to correctly identify points that preserve high level of accuracy. We have thus predicted the forthcoming time evolution of ground displacement over reclaimed platforms by combining DInSAR measurements and geotechnical-derived models, suggesting that approximately 90% of the settlements occur within about 15 years.